SEPSIS. Educational and Best Practice Frontiers. Beyond the Boundaries of Fatality, Enhancing Clinical Skills and Precision Medicine - Trovato G (Dove Medical Press, 2020)
Guglielmo Trovato The European Medical Association (EMA) and the School of Medicine, State University of Catania, Catania, ItalyCorrespondence: Guglielmo Trovato Email trovato.eu@gmail.comAbstract: Dissemination and exploitation of knowledge regarding affordable clinical skills and innovative precision medicine, two current topics in active development in medicine, may contribute to improve also sepsis management. Sepsis is a life-threatening organ dysfunction due to a dysregulated host response to infection. Sepsis is strongly related to all body organs or to systemic diseases and to the quality of the best-practice in use, which is particularly critical in surgical or intervention techniques. Trauma, surgical and mini-invasive procedures, vascular or endoscopic interventions, otolaryngology, obstetrics-gynecological and urological procedures, malnutrition, dental, skin, chronic liver, kidney and respiratory disease are frequently involved. Accordingly, apart from the clinical risk analysis and management of the process of care, the actual factors that may be easily neglected are the techniques used, the personal skills of the health professionals and the quality of the equipment. The quest for biomarkers consistent with the unmet needs of medical doctors and of their patient and the efforts for overcoming bacterial antibiotic resistances are currently the main foci of medical research. In addition, in this regard, research and innovation would benefit from greater knowledge, skills and use of bioinformatics and omics. The caveats related to in-silico approaches must be flagged: algorithms may equally warrant scientific innovations or hide the lack of them; a patient is more than a set of covariates. Epidemiology and prevention includes all the actions suitable for achieving an adequate hygiene and immunization of populations and for safer hospital policies and procedures during Patients’ stays. In any subset, the most unresolved critical point in sepsis is a timely diagnosis. This is impaired by low degrees of suspicion for the possibility of emerging sepsis, by the shortage of use of the simplest microbiological testing but, equally or more, by the insufficient diffusion of non-invasive imaging skills suitable to detect and monitor the emerging sites and sources of infection. In primary care, in emergency facilities, in hospital wards and in intensive care units, inclusion of appropriate knowledge, skills, expertise and imaging equipment must be extended as much as possible. The low cost of UltraSound machines and of increasing bioinformatics literacy by e-learning, makes such investments affordable even in limited-resources contexts. Frontier educational and best practice intervention enhancing affordable clinical skills and innovative precision medicine may lead beyond the boundaries of fatal outcomes in sepsis.Keywords: sepsis, bioinformatics, ultrasound, e-learning, MOOC, genomics, research models